2015
DOI: 10.1007/s10554-015-0736-5
|View full text |Cite
|
Sign up to set email alerts
|

Insights on atherosclerosis by non-invasive assessment of wall stress and arterial morphology along the length of human coronary plaques

Abstract: Wall stress (WS) is associated with high arterial pressure and affects the localization of atherosclerotic lesions. We sought to non-invasively investigate the distribution of WS along the length of human coronary arteries and investigate its potential effect on atherosclerosis in association with vascular stiffness, local arterial curvature and plaque volume. We reconstructed three-dimensionally 28 coronary arteries from 22 subjects who had undergone coronary computed tomography angiography. Coronary arteries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…To our knowledge, this is the first patient study quantifying coronary geometry during the cardiac cycle based on straightforward post-processing of four-dimensional non-invasive imaging data. Previous studies focusing on the relation between vessel geometry, corresponding hemodynamics [7][8][9]11], and plaque development [6,18,19,24] were often based on computational fluid dynamics and were thus accompanied by modeling assumptions requiring a considerable amount of time and computational capacity [6,25]. These studies found that hemodynamic and geometric parameters can be linked to (early) plaque development, but conclusions were drawn based on modeling or static approaches of the coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first patient study quantifying coronary geometry during the cardiac cycle based on straightforward post-processing of four-dimensional non-invasive imaging data. Previous studies focusing on the relation between vessel geometry, corresponding hemodynamics [7][8][9]11], and plaque development [6,18,19,24] were often based on computational fluid dynamics and were thus accompanied by modeling assumptions requiring a considerable amount of time and computational capacity [6,25]. These studies found that hemodynamic and geometric parameters can be linked to (early) plaque development, but conclusions were drawn based on modeling or static approaches of the coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…The novelty of this research resides in its uniqueness to quantify characteristics of movement of the coronary arteries during the cardiac cycle in a non-invasive and three-dimensional way, and in the derivation of new quantitative imaging biomarkers based on cCTA scans. This study did not investigate the relationship between the absolute coronary artery geometry values and CAD as this relationship has already been assessed previously [17][18][19]. The current study is exploratory.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, many other CFD studies have shown low WSS and high OSI are associated with atherosclerosis. In an adult coronary CT study, coronary segments with established plaque exhibited lower WSS compared to adjacent normal areas [53]. Within plaques, WSS was lower, and plaque volume was higher in mid-plaque compared to upstream and downstream areas (Figure 7) [53].…”
Section: Computational Fluid Dynamics Modeling Applied To the Study Omentioning
confidence: 99%
“…In an adult coronary CT study, coronary segments with established plaque exhibited lower WSS compared to adjacent normal areas [53]. Within plaques, WSS was lower, and plaque volume was higher in mid-plaque compared to upstream and downstream areas (Figure 7) [53]. In a study of carotid atherosclerosis, low time-averaged WSS and high OSI were seen in areas of increased mature plaque volume (Figure 8) [54].…”
Section: Computational Fluid Dynamics Modeling Applied To the Study Omentioning
confidence: 99%
See 1 more Smart Citation